Concern for Others and Perspective Taking on Moral Disengangement: Social Values as Moderator - Tahrir Tahrir (Psympathic : Jurnal Ilmiah Psikologi, 2022)
Previous reports have shown that there are several inconsistencies in the results of studies on the effect of concern for others and perspective-taking on moral disengagement. Therefore, this study aims to determine the effect of concern for others and perspective-taking on moral disengagement, moderated by social values among Islamic boarding school students in West Java. A causal correlation was used along with a structural design, involving 370 respondents. Data collection was carried out using the concern for others (CoF), perspective taking (PT), social values (SV), and moral disengagement (MD) scales. The results showed that social values played a significant role as a moderator variable in the effect of concern for others and perspective-taking on moral disengagement. Based on the results, social values had a role in reducing moral disengagement.